1990
DOI: 10.1037/0022-0167.37.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Relation of gender to power and involvement in supervision.

Abstract: Audiotaped supervision sessions from 40 master's level counselor trainees and 40 field placement supervisors were used in a content analytic study of the relation of supervisor and trainee gender to supervisory discourse. The Penman Classification Scheme was used to rate the middle 15 min of supervision on power and involvement dimensions. Classification cells were aggregated to yield high-power, low-power, and high-involvement categories. Transformed proportional data and kappa scores from sequential analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 35 publications
6
60
1
Order By: Relevance
“…They reported feeling motivated to improve their performance, as compared to female registrars who reacted according to whether the feedback was perceived as positive or negative criticism. Although female gender has been generally cited as a predictor for success in more affluent Western communities (Ferguson, James and Madeley 2002), the subordinate position of women (Davis and Allison 2013;Nelson and Holloway 1990) can account for these statistically significant results of the more positive perceptions of male versus female registrars in reporting on their experience of feedback. While internationally the numbers of women entering the medical field are increasing, there is still a disparity in their representation throughout, as well as in the higher echelons of the profession (Kilminster et al 2007) which may be attributed to their greater willingness to sacrifice their aspirations as compared to their male colleagues (Drinkwater, Tully and Dornan 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They reported feeling motivated to improve their performance, as compared to female registrars who reacted according to whether the feedback was perceived as positive or negative criticism. Although female gender has been generally cited as a predictor for success in more affluent Western communities (Ferguson, James and Madeley 2002), the subordinate position of women (Davis and Allison 2013;Nelson and Holloway 1990) can account for these statistically significant results of the more positive perceptions of male versus female registrars in reporting on their experience of feedback. While internationally the numbers of women entering the medical field are increasing, there is still a disparity in their representation throughout, as well as in the higher echelons of the profession (Kilminster et al 2007) which may be attributed to their greater willingness to sacrifice their aspirations as compared to their male colleagues (Drinkwater, Tully and Dornan 2008).…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to the fact that the power differences that exist between the sexes, that is evident in general conversation can also lead to the disempowerment of women in supervision. Female consultants are more likely to defer to their male colleagues, and in turn their subordinates, as a result of their own training experiences (Davis and Allison 2013;Nelson and Holloway 1990). Despite being correct, women often do not assert their rightful position of being the expert.…”
Section: Discussionmentioning
confidence: 99%
“…Some have reported that women and minority students typically have less access to mentoring and that good mentoring may help them gain advantages more frequently afforded to members of majority groups (Bogat & Redner, 1985;Cohen & Gutek, 1991;Gilbert & Rossman, 1992;Wilson & Johnson, 2001). Others have reported that women in academic settings are just as frequently mentored and just as satisfied with their mentorship as their male colleagues (Clark, Harden, & Johsnon, 2000;Fried et al, 1996), that ethnic minority students report greater satisfaction with their mentors than white counterparts (Mintz, Bartels, & Rideout, 1995), and that male and female mentors do not differ in providing for their protégés' career and psychosocial needs (Clark, Harden, & Johnson, 2000;Hollingsworth & Fassinger, 2002;Nelson & Holloway, 1990). …”
Section: Gender and Ethnicitymentioning
confidence: 99%
“…Nelson and Holloway (1990) found a similar pattern in their study of power balance in supervision, where both male and female supervisors assumed more power in supervision with female supervisees than with male supervisees. There is similar evidence of gender relevance in other domains.…”
Section: Supervision For Treatment Of Depression 10mentioning
confidence: 55%
“…It has been shown that we have different expectations (either implicit or explicit) of the abilities of men and women (Heilman, 2012), and that men are often seen as more competent than women (Ridgeway & Correll, 2004). For example, supervisors treat male and female supervisees differently -assuming a more powerful role with female supervisees than with Supervision for treatment of depression 5 males, and failing to reinforce females if they attempt to take a more powerful role themselves (Nelson & Holloway, 1990). Therefore, it can be hypothesised that supervisors will focus supervision differently for male and female supervisees, potentially focusing men more on the techniques of therapy because they see male therapists as more expert and competent than females.…”
Section: An Experimental Study Of the Role Of Therapist Gender And Anmentioning
confidence: 99%